Electrocoagulation for industrial wastewater treatment: an updated review. Issue 7 (14th June 2021) - Jing, Gaogui; Ren, Shuai; Pooley, Stephen; Sun, Wei; Kowalczuk, Przemyslaw B.; Gao, Zhiyong
Abstract : Electrocoagulation (EC) is a promising method that has been effectively employed in the treatment of various types of industrial effluents. Abstract : Electrocoagulation (EC) is a promising method that has been effectively employed in the treatment of various types of industrial effluent. Its distinct advantages such as good effluent quality, compact installation, simple operation and reduced sludge generation make it effective to treat numerous recalcitrant pollutants. To provide an overview of the current state and future potential of EC technology in industrial wastewater treatment, this paper presents a review of the most relevant recent publications. Aspects such as the characteristics, mechanism, and applicability of EC and factors affecting the EC efficiency are thoroughly reviewed. Additionally, the management of EC sludge as well as the development of emerging hybrid technologies are discussed systematically. This review highlights the applicability of EC in the treatment of real industrial wastewaters. In the long term, the EC treatment process will likely be recognized as one of the core methods for the treatment of various industrial effluents.